Cyber Physical Systems : model-based design : 9th International Workshop, Cyphy 2019, and 15th International Workshop, WESE 2019, New York City, NY, USA, October 17-18, 2019, Revised Selected Papers /: model-based design : 9th International Workshop, Cyphy 2019, and 15th International Workshop, WESE 2019, New York City, NY, USA, October 17-18, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available